Etiology of dyspnea in elite and recreational athletes - Hanks, C. D.; Parsons, J.; Benninger, C.; Kaeding, C.; Best, T. M.; Phillips, G.; Mastronarde, J. M. (The Physician and Sportsmedicine, 2012)
Background: Breathing complaints are common in athletes. Studies have suggested that the prevalence of asthma and exercise-induced bronchoconstriction (EIB) is higher in elite athletes than the general population. Vocal cord dysfunction (VCD) may mimic asthma and EIB as a cause of dyspnea in athletes. However, the majority of studies to date have primarily relied on symptoms to diagnose VCD, and there are limited data on coexistence of asthma, EIB, and/or VCD. It is well established that symptoms alone are inadequate to accurately diagnose EIB and VCD. Our goal was to define via objective testing the prevalence of asthma, EIB, VCD alone, or in combination in a cohort of athletes with respiratory complaints. Methods: A retrospective chart review was done of 148 consecutive athletes (collegiate, middle school, high school, and recreational) referred to a tertiary care center`s asthma center for evaluation of respiratory complaints with exercise. An evaluation including medical history, physical examination, and objective testing including pulmonary function testing (PFT), eucapnic voluntary hyperventilation, and video laryngostroboscopy, were performed. Results: The most common symptom was dyspnea on exertion (96%), with < 1% complaining of either hoarseness or stridor. The most common diagnosis prior to referral was asthma (40%). Only 16% had PFTs prior to referral. Following evaluation by a pulmonologist, 52% were diagnosed with EIB, 17% with asthma, and 70% with VCD. Of those diagnosed with asthma before our evaluation, the diagnosis of asthma was confirmed, with PFTs in only 19 of 59 (32%) athletes based on our testing. Vocal cord dysfunction was more common in females and in adolescent athletes. Coexistence of multiple disorders was common, such as EIB and asthma (8%), EIB and VCD (31%), and VCD and asthma (6%). Conclusions: Asthma and EIB are common etiologies of dyspnea in athletes, both competitive and recreational. However, VCD is also common and can coexist with either asthma or EIB. Vocal cord dysfunction may contribute to exercise-related respiratory symptoms more frequently in middle school- and high school-aged athletes than in college athletes. Effective treatment of dyspnea requires appropriate identification and treatment of all disorders. Classic symptoms of stridor and/or hoarseness are often not present in athletes with VCD. Accurate diagnosis of asthma, EIB, and VCD requires objective testing and can prevent exposure of patients to medications that are ineffective and have potential adverse side effects. Furthermore, there is need for increased awareness of VCD as a common cause of respiratory complaints in athletes, either as a single diagnosis or in combination with EIB, especially in females, as well as middle school and high school athletes.